العمل عن بعد ودوره في تشغيل ذوي الإحتياجات الخاصة في محافظة أربيل (المجلة العراقية للعلوم الاقتصادية, 2018)
The list of contemporary concepts and mechanisms will be lengthening, and became a popular in the last decades of the twentieth century, which they need to be under scientific investigation to reach to the correct meanings, and know how to use them to solve economic and social problems, the clear examples of that is the advantages of information and communication technology, which created a new and modern ways of doing business, especially the so-called teleworking E-Work or work at Home, which are deal with the fact that there are broad areas for the execute of some jobs without the need for a physical presence of work parties at workplace.The study put forward a set of questions, and sought to answer them through specific hypotheses, using a theoretical study and available statistical data and special questionnaire , the study reach to a number of conclusions, most notably the difficulty of distinguishing between work at home, normal work at labor offices, with the emergence of more flexible and independent working methods for offices, including those with special needs which spent a big part of their working time outside the traditional office, that well be conventionally acceptable.The study presented a set of proposals, including the approval of draft projects for the work of people with special needs, especially new labor code laws and the Social Security Act to provide adequate and decent working environment and guarantees to encourage this group to work in the public and private sector, so as to enhance their role in the overall economy.Key Words: teleworking, disabilities, employment systems, difficulties in the application of teleworking, Attitudes of disabilities towards telework, Qualifications of disabilities in Erbil province.